Pelatihan Aplikasi Laporan Keuangan atas Standar Akuntansi PSAK 1 Pada BUMDes Guna Mencapai Tujuan Berkelanjutan SDGis - Hertati, Lesi; Yadiati, Winwin; Asharie, Asmawati; Heriyati, Agustina (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
The aim of PKM training is to implement applications to support the achievement of Sustainable Development Goals (SDGs) in BUMDes. The presentation of financial reports to BUMDes by Indo Global Mandiri University lecturers involved three (3) lecturers and four (4) students so that students could put into practice the theories they had gained from studying in the industrial world. The results of PKM activities are so that BUMDes can make financial reports guided by PSAK 1, namely transparent and accurate, for stakeholders to understand the use and management of resources better. This application can help BUMDes to manage and present financial reports more efficiently, saving time and resources that can be allocated to activities that support the achievement of sustainable goals, namely Sustainable Development Goals (SDGs) at BUMDes in accordance with applicable accounting standards and regulations while still complying with regulations. and minimize the risk of non-compliance. Through financial reports produced by BUMDes, BUMDes can monitor financial performance over time, identify trends and patterns that can assist in decision making to achieve sustainable goals. The application of financial reports that are presented in a structured and accurate manner for BUMDes can increase access to external financial resources, such as loans or grants, which can be used to support initiatives.